A theoretical investigation into the comparative adsorption between dissolved oxygen and oxygenate species on zeolite 3.7 Å during aviation fuel treatment for thermal stability improvement. (1st June 2022) - Alborzi, Ehsan; Flyagina, Irina S.; Mielczarek, Detlev C.; Blakey, Simon G.; Pourkashanian, Mohamed
Abstract: In this work we present a theoretical investigation to promote our understanding of the underlying processes of chabazite supported fuel treatment to improve thermal stability at the laboratory scale. It has been shown in prior work that zeolites can remove oxygenated heteroatomic species as well as molecular oxygen from fuel. This work investigates the molecular interaction of the aforementioned species with zeolite to provide a theoretical framework to robustly describe the experimentally observed behaviour. The ab initio quantum chemistry calculations show that a variety of interactions can occur. This work correlates observed enthalpy changes between different oxygenated species and oxygen to their propensity to be removed from the fuel during zeolite treatment which can act as a predictor for the propensity of contaminants to be removed by the zeolite. Highlights: Theoretical investigation of fuel preconditioning with zeolites. Fuel treatment by zeolite adsorption for improved thermal stability. Elucidation of underlying mechanism of oxygen/polar species removal by zeolites. Interdisciplinary approaches to improve our understanding of fuel thermal stability.